EVALUASI EFEKTIVITAS FUNGSI SATUAN PENGAWAS INTERN (SPI) DALAM MELAKSANAKAN AUDIT INTERNAL - OCTAVA PRATIVI, RYKE Octava (Jurnal Akuntansi AKUNESA, 2013)
The purpose of this study was to determine how the implementation, effectivenessand efficiency of the Internal Supervisory Unit of the PT. XYZ in conducting internal auditin the company. The study was conducted using qualitative methods and two types ofresearch data, the primary data and secondary data obtained in natural conditions(natural setting). Primary data is collected by interviewing deeply the interviewees, thatwas implementation and documentation team of ISO 2008 : 9001 (in depth interview).Secondary data obtained through literature sources such as the Report of Inspection andQuality Management System ISO 2008 : 9001. To sharpen the study result, research objecttaken and observed is about the performance of the Internal Supervisory Unit inoverseeing the implementation of operational activities based on ISO 2008 : 9001 inGovernment Marketing Unit Project. The results showed an understanding of theprocedure has not been fully implemented Quality Management, as well as on contractsthat have not been conducted according to standards in terms of quality procedures of ISO2008 : 9001 which is contain of procedure related with customer.Keyword: Unit Supervisor Intern, Organization for Standardization (ISO)